Performance, limitation, and opportunities of acid-resistant nanofiltration membranes for industrial wastewater treatment - Lee, Jae Won; Shin, Yeojin; Boo, Chan hee; Hong, Seungkwan (Elsevier BV, 2023)
Various industrial activities generate highly acidic wastewaters, posing a particular concern due to their large volume, environmental impact, and limited disposal options. Nanofiltration (NF) has the potential to provide energy-, cost-, and space-effective solutions for wastewater treatment at industrial sites. However, conventional thin-film composite NF membranes degrade under acid exposures, largely limiting their applications in industrial wastewater treatment. Development of chemically robust NF membranes that are stable during operation with highly acidic feed streams has been a subject of active research and industrial interest. In this critical review, we first provide a comprehensive survey for the broad spectrum of industrial processes that yield acidic wastewaters. We then conduct in-depth analyses for short-and long-term rejection performances and stabilities of commercial NF membranes, especially under low solution pH conditions. Several key mechanisms responsible for the degradation of semi-aromatic polyamide networks by acid-catalyzed hydrolysis are discussed to highlight the limitation of commercially available NF membranes. Finally, we describe a wide variety of technical strategies to fabricate acid-resistant NF membranes, focusing on the key mechanism to enhance acid stability. We conclude by providing useful insights to guide the future directions for academic studies as well as industrial applications of acid-resistant NF membranes.